Adquisició de primeres i segones llengües: perspectiva històrica i qüestions actuals - Comajoan Colomé, Llorenç (Caplletra. Revista Internacional de Filologia, 2003)
This article discusses theoretical approaches to language acquisition and language teaching and focuses on recurring themes in these approaches and how they have developed over time. The first section provides a historical overview of the history of language acquisition. The second section reviews the development of three contemporary issues that originated in past philosophical and linguistic discussions: the differences between first and second language acquisition and the poverty of the stimulus argument, innatism versus empiricism, and the effect of language instruction in second language acquisition. The article concludes with an emphasis on the interdisciplinary nature of language acquisition study.